Narrative biography: meaning making through painting / Syamrul Nizam Abdul Malek - Abdul Malek, Syamrul Nizam (2010)
Historically, narrative has been a highly prominent feature of visual art. Artist today continue to engage with narrative, for storytelling will always be a powerful medium for human expression. Thus, this research is conducted to find out and understand what are the characteristics or concepts that are structurally used in narrative works. Other than that this research is also done to understand the nature of how different artist have use the narrative concept in portraying their work as a storytelling subject whether in dealing with personal experience, popular culture, fantasying, fiction and world (historical) event. Finally, this research is conducted to understand how all of this information can be used to better comprehend the researcher’s own work, which cover an understanding of pictorial, and image structure and concerning with its meaning making. Artists such as David Salle, Cindy Sherman, Eleanor Antin, Gregory Crewdson, Laurie Simmons, Christian Boltanski, Tim Barney, Jailani Abu Hassan and Ismail Zain were studied to see how they have conveyed narrative art as the basis of their conceptual framework. By conducting literature research from the secondary data, the research will also go into the process of ‘Art Making’, which will cover two important factors, the making of the ‘Art object’ and the ‘Meaning’. Here two aspects will be looked into. Firstly the ‘Formal and Material’ (art object) and secondly the ‘Content and Context’ (Meaning). By doing this and going through the research inquires and process, the researcher has used all of this information and knowledge in further understanding the researcher’s own work and turning it into a useful data for those who would be interested in narrative art.